Medicine in Ancient – Egypt - Supady, Jerzy (Health Promotion & Physical Activity, 2019)
The history of ancient Egypt covers three millennia before the birth of the Christ. Information about medicine in that country, mainly found in papyrus, prove the occurrence of diseases known today and magic-rational therapy used by Egyptian physicians - priests.